“Strategic and Financial Management Integration in Enhancing Banks’ Competitive Advantage” (Al-Mansour Journal, 2026)
This research aims to study the relationship between the integration of strategic and financial management and its role in enhancing the competitiveness of Iraqi government banks, particularly Al-Rafidain and Al-Rasheed banks in Baghdad, within a rapidly changing and increasingly competitive banking environment. The research adopted a descriptive-analytical approach, and primary data were collected through a questionnaire specifically designed to measure the two study variables. The questionnaire was distributed to a purposive sample of (60) employees and administrators in two government banks in Baghdad: Al-Rafidain Bank and Al-Rasheed Bank. The data were analyzed using the Statistical Package for the Social Sciences (IPSS, Version 20). The strategic and financial management integration variable was measured through four main dimensions: integration between strategic and financial planning, integration in strategic and financial decision-making, integration in resource management and capital allocation, and integration in control systems and performance evaluation. The competitiveness enhancement variable was measured through the operational and financial efficiency dimensions within the government framework, the quality of banking services in the public sector, and the trust and institutional reputation of the government bank. The results of the statistical analysis, using multiple regression analysis, showed a significant impact of strategic and financial management integration, with its four dimensions combined, on enhancing the competitiveness of banks. The coefficient of determination (R²) indicated that the strategic and financial management integration variables explain 80.4% of the variance in enhancing the competitiveness of the banks studied. The research concludes that strategic and financial management integration is a fundamental framework for enhancing the competitiveness and sustainability of Iraqi government banks. It recommends adopting this integration as a comprehensive management approach in Al-Rafidain and Al-Rasheed banks to improve banking performance and support financial stability and economic development.
Keywords: Strategic management; banking; financial performance; competitiveness; resource management